Amorphophallus muelleri Blume Shoot Induction on Different Media Types and Plant Growth Regulator Combinations - Oktavia, Gebby Agnessya Esa; Junairiah, Junairiah; Manuhara, Yosephine Sri Wulan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Conventional propagation experiences problems due to long period for seed production, disease contamination, low reproductive rate and season dependent. In vitro propagation offers several advantages. This research aims to assess the impact of different media types and the concentrations of BAP and IBA on the in vitro growth and development of A. muelleri shoots. Bulbil explants were cultivated using MS media with different media types (solid media, agitated liquid media, and static liquid media) with various BAP and IBA concentration treatments (1 mg/l, 2 mg/l, and 3 mg/l). The results demonstrated that the media type and combinations of BAP and IBA treatments significantly influenced period of callus formation and the number of shoots. The development of explant on both solid and static liquid media involves initial explant swelling, formation of nodular callus, greenish buds, and ultimately shoots. Anatomical observation showed that explants experienced indirect organogenesis, characterized by the presence of pre meristem nodular callus, meristematic tissue, apical meristem and leaf primordia. The agitated liquid media didn’t promote growth and development of the explants. The most effective combination was found to be the static liquid media supplemented with 3 mg/l BAP and 1 mg/l IBA.